2021
DOI: 10.1002/ps.6281
|View full text |Cite
|
Sign up to set email alerts
|

Field validation of biocontrol strategies to control brown rot on stone fruit in several European countries

Abstract: BACKGROUND Brown rot caused by Monilinia spp. is the most significant disease of stone fruit. New approaches to fruit production have necessitated the development of control strategies that are more eco‐ and consumer‐friendly. An efficient field strategy to control brown rot was previously designed based on the application of two biocontrol agents (BCAs), Bacillus amyloliquefaciens CPA‐8 (CPA‐8) or Penicillium frequentans 909 (Pf909), with calendar‐based treatment. In the present study, the strategy was valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…Mean daily temperature (black line), amount of rainfall (black bars), and relative humidity (dotted line) were recorded during the trials. Daranas et al 10.3389/fmicb.2023.1324965 Frontiers in Microbiology frontiersin.org rates of A17 in the field are consistent with those reported by other authors monitoring B. amyloliquefaciens CPA-8 biocontrol strain, that highlighted its ability to survive largely on leaves and fruit surfaces after preharvest application in the field (Gotor-Vila et al, 2017;Vilanova et al, 2018;Casals et al, 2021). These results are consistent with the fact that the spore-forming ability of Bacillus species provides high resistance to field environmental conditions (Mendis et al, 2018), making this genus a good candidate for developing stable and efficient biocontrol products.…”
Section: Discussionsupporting
confidence: 87%
“…Mean daily temperature (black line), amount of rainfall (black bars), and relative humidity (dotted line) were recorded during the trials. Daranas et al 10.3389/fmicb.2023.1324965 Frontiers in Microbiology frontiersin.org rates of A17 in the field are consistent with those reported by other authors monitoring B. amyloliquefaciens CPA-8 biocontrol strain, that highlighted its ability to survive largely on leaves and fruit surfaces after preharvest application in the field (Gotor-Vila et al, 2017;Vilanova et al, 2018;Casals et al, 2021). These results are consistent with the fact that the spore-forming ability of Bacillus species provides high resistance to field environmental conditions (Mendis et al, 2018), making this genus a good candidate for developing stable and efficient biocontrol products.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, our findings showed better results than Candida sake CPA‐1 with 37% efficacy of Botrytis cinerea on grape berry fruits 18 . However, it is important to mention that the incidence of the diseases and the effectiveness of the biocontrol agents depend on the environmental conditions and the density of pathogens in the field 6 …”
Section: Discussionsupporting
confidence: 64%
“…Few attempts have been made in the biological control of M. fructigena; some of them are described by Batra in 1977 (Hrustić et al, 2012), including experiments with Trichoderma viride has not been prepared for commercial application. Some practical applications of the bacteria Bacillus subtilis and Pseudomonas cepacia in strawberries [Fragaria ananassa] and sweet cherries [P. avium] have been made.It was also shown that isolates of Aureobasidium pullulans, Epicoccum purpurascens, Sordaria fimicola, and Trichoderma polysporum, applied individually or in mixtures to wounded apples, gave good protection from infection of M. fructigena (Lahlali et al, 2020).Some experiments have been undertaken in commercial orchards involving control of twig blight and fruit rot of peaches and plums [P. domestica] due to M. laxa by the application of fungal antagonists such as E. nigrum, Penicillium frequentans, or Penicillium purpurogenum (Martini and Mari, 2014;Ortega et al, 2019), or the control of fruit rot of peaches induced by M. fructicola using B. subtilis (Casals et al, 2021). These antagonists may also be effective against M. fructigena.…”
Section: Tebuconazolementioning
confidence: 99%